ANALISIS KEDISIPLINAN BELAJAR SISWA KELAS V SD 2 MUHAMMADIYAH KARANGPAWITAN GARUT - Sopiah, Ai; Gunawan, Dani; Asti Pujiasti, Dea (Bale Aksara, 2021)
School is an effective place for the formation of individual character. Since long time ago, schools have had the main goal in the field of education, namely to form intelligent humans who have good character and character. This study aims to describe the implementation of the rules and discipline of student learning at SD 2 Muhammadiyah Tabrik Karangpawitan. This research is a qualitative descriptive research. The research subjects were teachers and students of SD 2 Muhammadiyah Tabrik Karangpawitan. The object of this research is the implementation of student learning rules and discipline. This study used data collection techniques in the form of questionnaires, interviews, and documentation. The data analysis used Miles and Huberman's analysis techniques (data reduction, data display, and conclusion drawing). The data validity test used technique and source triangulation. The results showed that the implementation of rules and learning discipline at SD 2 Muhammadiyah Tabrik Karangpawitan, includes three aspects, namely planning, implementation, and evaluation.